2017
DOI: 10.1007/s11096-017-0429-3
|View full text |Cite
|
Sign up to set email alerts
|

A clinical prediction model for infusion-related reactions to rituximab in patients with B cell lymphomas

Abstract: Background Infusion-related reactions (IRRs) are a major adverse event of rituximab. Objective To develop a prediction model for IRRs to rituximab among patients with B cell non- Hodgkin's lymphomas (B-NHL). Setting A 1000-bed university hospital in Tokyo. Methods Patients with B-NHL treated with rituximab at our institution from 2004 to 2014 were retrospectively analysed. Chills, fever, rash, nausea, asthenia, headache, cardiovascular symptoms, and respiratory symptoms of any grade, in association with rituxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Previously, Paul and Cartron [26] reported lymphocyte count, bulky disease, low-grade B-cell NHL, the level of CD20 expression on CLL cells, and Fc/Fc gamma receptor (FcγR)-mediated interactions between natural killer (NK) cells and CD20+ cells as being associated with the occurrence of IRRs. In the observational setting in patients with hematologic malignancies, predictive indicators of rituximab IRRs have included bone marrow involvement, body weight, low-grade lymphomas, and bulky disease [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Paul and Cartron [26] reported lymphocyte count, bulky disease, low-grade B-cell NHL, the level of CD20 expression on CLL cells, and Fc/Fc gamma receptor (FcγR)-mediated interactions between natural killer (NK) cells and CD20+ cells as being associated with the occurrence of IRRs. In the observational setting in patients with hematologic malignancies, predictive indicators of rituximab IRRs have included bone marrow involvement, body weight, low-grade lymphomas, and bulky disease [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary outcomes were the overall incidence of IRRs to the rst and second cycles of rituximab, the infusion rates of rituximab during the onset of an IRR, the conversion rate to short infusion at the third cycle in each group, and the overall conversion rate to short infusion at the third cycle. We set the target number of patients as 70 to validate IRR incidence in each risk group; this was half the number selected for our previous study, in which approximately 40% of the patients experienced IRRs to rituximab [7]. The sample size was equivalent to the minimum required to detect a 30% reduction in IRR incidence in all patients with 80% power and 10% alpha error based on a one-sided test.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that low-grade histology and bulky disease with a tumor diameter > 10 cm are independent risk factors for IRRs to rituximab [7]. However, to the best of our knowledge, no prospective or retrospective studies have evaluated a novel protocol that can minimize IRRs to rituximab among B-NHL patients with various risk factors.…”
Section: Impact Of Findings On Practicementioning
confidence: 96%
See 2 more Smart Citations